Myocardial ultrastructure can augment genetic testing for sporadic dilated cardiomyopathy with initial heart failure. (6th September 2021) - Saito, Tsunenori; Sato, Naoko Saito; Mozawa, Kosuke; Adachi, Akiko; Sasaki, Yoshihiro; Nakamura, Kotoka; Oka, Eiichiro; Otsuka, Toshiaki; Kodani, Eitaro; Asai, Kuniya; Mizuno, Kyoichi; Shimizu, Wataru; et al.
Abstract: Aims: The aim of the present study was to consider whether the ultrastructural features of cardiomyocytes in dilated cardiomyopathy can be used to guide genetic testing. Methods and results: Endomyocardial biopsy and whole‐exome sequencing were performed in 32 consecutive sporadic dilated cardiomyopathy patients [51.0 (40.0–64.0) years, 75% men] in initial phases of decompensated heart failure. The predicted pathogenicity of ultrarare (minor allele frequency ≤ 0.0005), non‐synonymous variants was determined using the American College of Medical Genetics guidelines. Focusing on 75 cardiomyopathy‐susceptibility and 41 arrhythmia‐susceptibility genes, we identified 404 gene variants, of which 15 were considered pathogenic or likely pathogenic in 14 patients (44% of 32). There were five sarcomeric gene variants (29% of 17 variants) found in five patients (16% of 32), involving a variant of MYBPC3 and four variants of TTN . A patient with an MYBPC3 variant showed disorganized sarcomeres, three patients with TTN variants located in the region encoding the A‐band domain showed sparse sarcomeres, and a patient with a TTN variant in encoding the I‐band domain showed disrupted sarcomeres. The distribution of diffuse myofilament lysis depended on the causal genes; three patients with the same TMEM43 variant had diffuse myofilament lysis near nuclei ( P  = 0.011), while two patients with different DSP variants had lysis in the peripheral areas of cardiomyocytes ( P  = 0.033). Conclusions: Derangement patterns of myofilament and subcellular distribution of myofilament lysis might implicate causal genes. Large‐scale studies are required to confirm whether these ultrastructural findings are related to the causative genes.